PREDICTION OF BRAND AWARENESS ON PURCHASING DECISIONS: BRAND IMAGE AS MEDIATION - Sudarwati, Sudarwati; Aprian Aditama, Rizky Ramadhan; Susanto, Ryan; Tias, Riris Wahyuning (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to examine and analyze the effect of brand ambassadors and brand awareness on purchasing decisions and measure the role of brand image as a mediating variable in the influence of brand ambassadors and brand awareness on purchasing decisions on Erigo products. This model involves training variables as supporting variables. This research was applied to consumers of Erigo products in the Greater Solo area, the sample taken amounted to 100 respondents, with sampling using purposive sampling technique. This research was analyzed using Partial Least Square (PLS) with SmartPLS3 software. The results showed that brand ambassadors have a positive and significant effect on brand image. Brand ambassadors have a positive and significant effect on purchasing decisions. Brand awareness has a positive and significant effect on brand image. Brand awareness has a positive and significant effect on purchasing decisions. Brand image has a positive and significant effect on purchasing decisions. Brand ambassadors through brand image mediation have no significant effect on purchasing decisions. And brand awareness through brand image mediation has a positive and significant effect on purchasing decisions. Keywords: Brand Image, Purchase Decision